A First Course in Engineering Drawing - Rathnam, K. (Springer Singapore, 2018)
The primary objective of this book is to provide an easy approach to the basic principles of Engineering Drawing, which is one of the core subjects for undergraduate students in all branches of engineering. Further, it offers comprehensive coverage of topics required for a first course in this subject, based on the author's years of experience in teaching this subject. Emphasis is placed on the precise and logical presentation of the concepts and principles that are essential to understanding the subject. The methods presented help students to grasp the fundamentals more easily. In addition, the book highlights essential problem-solving strategies and features both solved examples and multiple-choice questions to test their comprehension.